2010
DOI: 10.1007/s00210-010-0525-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo growth inhibition of sarcoma 180 by latex proteins from Calotropis procera

Abstract: Latex of Calotropis procera has been described as a relevant source of pharmacologically active proteins, including proteins with anticancer activity. A previous in vitro study of laticifer proteins (LP) from C. procera reported that they had selective cytotoxic effects on human cancer cell lines. The aim of this study was to determine the effects of LP in vivo using mice transplanted with sarcoma 180. Biochemical, hematological, histopathological, and morphological analyses were performed in animals given LP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…It was shown to inhibit DNA synthesis, probably affecting topoisomerase I activity, leading to apoptosis in tumor cells (Oliveira et al, 2007). Recently, its in vivo anticancer potential was also evaluated, reinforcing the potential of laticifer proteins in treating neoplasia (Oliveira et al, 2010). Furthermore, HdLP acts as an immunomodulatory agent, raising the production of OVA-specific antibodies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was shown to inhibit DNA synthesis, probably affecting topoisomerase I activity, leading to apoptosis in tumor cells (Oliveira et al, 2007). Recently, its in vivo anticancer potential was also evaluated, reinforcing the potential of laticifer proteins in treating neoplasia (Oliveira et al, 2010). Furthermore, HdLP acts as an immunomodulatory agent, raising the production of OVA-specific antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…The latex of Himatanthus sucuuba increased nitric oxide (NO) and tumor nuclear factor-␣ (TNF-␣) and decreased transforming growth factor-␤ (TGF-␤) production in macrophages, suggesting an immunomodulatory activity (Soares et al, 2010). In the family Apocynaceae, experimental studies with proteins of the latex of C. procera suggested that the active LP fraction (PII) displays in vivo inhibition of tumor growth, probably by mediating an increased immunopharmacological response (Oliveira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The gels were then incubated in 50 mM acetate buffer (pH 5.0) in the presence or absence of 3 mM DTT for 16 h at 37 °C. The enzymatic activity was detected as transparent bands on the gel (Oliveira et al, 2010).…”
Section: Detection Of Proteinases By Zymographymentioning
confidence: 99%
“…Many publications have described the pharmacological activities displayed by various plant proteins (Hale et al, 2005, Oliveira et al, 2010, including those belonging to the Leguminoseae family (Leite et al, 2012). These plant proteins receive special attention, as they are promising molecules for human therapeutic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The latex is commonly known as a rich source of active compounds bearing pharmacological properties (Dewan et al, 2000;Kumar et al, 2001;Frade et al, 2004;Chin et al, 2006). In traditional medicine, the latex of different plant inflammatory and pain process as well as tumor growth (Alencar et al, 2004;Soares et al, 2005;Oliveira et al, 2010). In these studies, the latices were collected in water and submitted to centrifugation and dialysis steps to obtain a protein fraction free of rubber and small molecules.…”
Section: Introductionmentioning
confidence: 99%